Bibliometric analysis of highly cited publications in health policy and Services. Issue 1 (2nd January 2020) - Hsu, Y-Hsin Elsa; Yang, Ya-Ting; Wang, Ming-Huang; Ho, Yuh-Shan
Abstract : The present study is to identify and analyse the characteristics of the highly cited articles in Web of Science category of health policy and services, within the publication year from 1923 to 2017 based on Social Science Citation Index. Highly cited articles that have been cited 100 times or more from Web of Science Core Collection since their publication year to the end of 2017 were analyzed. Publication year, authors, institutions, countries, journals, and citation life cycles were used to evaluate the publication performance of the highly cited articles. Four citation indicators were applied to evaluate highly cited articles. Six publication indicators were also used to compare performance of countries and institutions. A publication performance indicator, the Y-index, was applied to assess publication potential and the characteristics of authors. A relationship between number of articles in each year and their citations per publication by years was proposed for distribution of highly cited articles. Results showed that highly cited articles published in journals with not only higher journal impact factor but also lower one. The US and Harvard University ranked top in six publication indicators respectively. Y-index results showed that J.H. Hibbard had highly cited articles publication potential. In addition, each of the high impact classic articles in 2017 were summarized.